Kesalahan Penggunaan Huruf Kapital dan Tanda Baca dalam Menulis Tegak Bersambung pada Tema 6 SD Negeri Jombang 05 Kabupaten Jember - Denny Dwi Permatasari; Hari Satrijono; Fitria Kurniasih (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2021)
This study aims to determine the percentage and the factors that influence the use of capital letters, punctuation, and cursive writing errors for second grade students of SD Negeri Jombang 05 Jember. The title of this research is the Error in Using Capital Letters and Punctuation in Upright Concatenated Writing on Theme 6 Class II SD Negeri Jombang 05 Jember Regency. The background of this research is that in cursive writing there are still students' language errors, namely the use of capital letters, punctuation marks, and cursive writing. This type of research design is qualitative research, while the type of research used is descriptive research. The method used is the interview and documentation method. Data analysis techniques consist of: (1) data reduction; (2) data presentation; and (3) drawing conclusions. The subjects of this study were the second grade students of SD Negeri Jombang 05, Jember Regency, totaling 19 students, 11 male students and 8 female students.The results and discussion in this study indicate that the types of errors consist of: Errors in the use of capital letters in the ability to write cursive are included in the low category with a percentage of 19.84%. Errors in the use of punctuation marks on the ability to write in cursive are included in the low category with a percentage of 25.26%. Writing errors in the form of letters in the ability to write in cursive are included in the very low category with a percentage of 5.16%. The factors that cause errors made by students in the use of capital letters, punctuation marks, and cursive writing are errors and mistakes. The conclusion of this study is that the errors in the use of capital letters, punctuation marks, and writing in cursive, cursive, and overall students are still low.